Prevalência de atividade física no lazer dos escolares de 3 escolas do ensino médio da rede de ensino estadual urbana na cidade de Parintins - (:unkn) unknown (ICSEZ - Instituto de Ciências Sociais, Educação e Zootecnia (Parintins), 2025)
This study addresses leisure-time physical activity among students from three public schools in the city of Parintins, Amazonas. The research aimed to analyze the prevalence of sufficient leisure-time physical activity among high school students from the urban state school system in the city of Parintins, as well as its associations with socioeconomic, demographic, and behavioral variables. The method used for data collection consisted of an instrument specifically designed for the research, which collected information on demographics (sex, age, date of birth, place of birth, and neighborhood of residence in Parintins), socioeconomic aspects (ownership of goods in the household), behavioral aspects (means of transportation used to go to and from school), physical activity (active commuting to and from school, physical activity in free time, participation in physical education classes, overall physical activity, and willingness to practice physical activity), and sedentary behavior (weekly time sitting, watching television, and using screens). During data collection in the classes, the instrument was given to each student, who completed it according to the reading of the statements by the responsible team. The results obtained in this study show that 83.1% of students are insufficiently active and only 16.9% of them are physically active, which shows the alarming prevalence of physical inactivity among schoolchildren in the city of Parintins, AM. It is concluded that promoting an active lifestyle is crucial for the formation of a healthier generation, contributing to the prevention of chronic diseases and improving the quality of life of the young population in Parintins. Therefore, it is imperative that initiatives are integrated and sustainable, aiming at building a healthier and more active future for adolescents in the region.
Prevalence of leisure-time physical activity among students from 3 high schools in the urban state education network in the city of Parintins
Keywords: Atividade física; Escolares; Qualidade de vida; Fatores socioeconômicos; Physical activity; Schoolchildren; Quality of life; Socioeconomic factors; CIENCIAS DA SAUDE: EDUCACAO FISICA; .; .